Seismic retrofit of George Massey Tunnel. - Taylor, Peter R. (Earthquake engineering & structural dynamics.)
The 629 m long immersed George Massey Tunnel passes nder the south arm of the Fraser River near Vancouver, British Columbia. The tunnel was completed in 1959. Based on current seismic design standards, the precast concrete structure is grossly under-reinforced in the longitudinal direction. Buckland & Taylor Ltd was retained by the Ministry of Transportation of British Columbia to conduct a seismic assessment and final design for the seismic safety retrofit of the tunnel. A number of vulnerabilities were identified including soil liquefaction in the loose jetted sand and native deposits underneath the tunnel, resulting in tunnel flotation, large differential lateral displacements and post-liquefaction consolidation settlements, subsequently imposing large tensile and compressive forces in the weak tunnel joints. The situation of cracking and water leakage potentially creates a life hazard in the event of a major earthquake. During the final design, detailed non-linear dynamic geotechnical analyses were conducted to study the effects of soil liquefaction and to evaluate ground improvement measures. Detailed structural analyses were also conducted considering different proposed retrofit schemes to enable the tunnel section to handle the soil displacement demands. Centrifuge model testing was used to calibrate and verify the liquefaction characteristics predicted by the numerical models and the proposed densification and gravel drainage techniques. Field testing of gravel drains was performed to collect data on the performance of different types of gravel drains.